Dose-response relationships of the sigmoid for urgency syndrome after gynecological radiotherapy. (3rd October 2018) - Alevronta, Eleftheria; Skokic, Viktor; Wilderäng, Ulrica; Dunberger, Gail; Sjöberg, Fei; Bull, Cecilia; Bergmark, Karin; Jörnsten, Rebecka; Steineck, Gunnar
Abstract: Purpose: To find out what organs and doses are most relevant for 'radiation-induced urgency syndrome' in order to derive the corresponding dose–response relationships as an aid for avoiding the syndrome in the future. Material and methods: From a larger group of gynecological cancer survivors followed-up 2–14 years, we identified 98 whom had undergone external beam radiation therapy but not brachytherapy and not having a stoma. Of those survivors, 24 developed urgency syndrome. Based on the loading factor from a factor analysis, and symptom frequency, 15 symptoms were weighted together to a score interpreted as the intensity of radiation-induced urgency symptom. On reactivated dose plans, we contoured the small intestine, sigmoid colon and the rectum (separate from the anal-sphincter region) and we exported the dose-volume histograms for each survivor. Dose–response relationships from respective risk organ and urgency syndrome were estimated by fitting the data to the Probit, RS, LKB and gEUD models. Results: The rectum and sigmoid colon have steep dose–response relationships for urgency syndrome for Probit, RS and LKB. The dose–response parameters for the rectum were D50 : 51.3, 51.4, and 51.3 Gy, γ50  = 1.19 for all models, s was 7.0e −09 for RS and n was 9.9 × 10 7 for LKB. For Sigmoid colon, D50 were 51.6, 51.6, and 51.5 Gy, γ50 were 1.20, 1.25, and 1.27, s was 2.8 for RS and n was 0.079 for LKB. Conclusions: Primarily the dose to sigmoid colon as well as the rectum is related to urgency syndrome among gynecological cancer survivors. Separate delineation of the rectum and sigmoid colon in order to incorporate the dose–response results may aid in reduction of the incidence of the urgency syndrome.